Pragmatic Skills in Nonverbal Identical Twins with Autism Spectrum Disorders - Shilpashri H.N.; Shyamala Chengappa (Journal of All India Institute of Speech and Hearing, 2008)
The present study investigated the use of six pragmatic language skills by a pair of five year old male identical twins with autism spectrum disorders during the course of a session of mother-child interaction. Frequency of each pragmatic language skill used by the mother along with type and frequency of pragmatic language skills used by the two subjects were analyzed. Results showed similarities in use of pragmatic skills in both. However, differences existed with respect to frequency of use.